Studi Eksperimen: Penerapan Komik Elektronik dalam Meningkatkan Minat Belajar Ekonomi pada Siswa SMA Negeri 3 Pasuruan - Shalikha, Putri Ayu Anisatus; Andianto, M. Mascun; Kinasih, Andjani Sulistyaningrum; Priatmini, Ria (Universitas Hamzanwadi, 2024)
At SMA Negeri 3 Pasuruan, Economics is an elective subject for pupils in Grade XI. The students consciously choose economics as one of the subjects that they want to study in more depth. Nevertheless, the enthusiasm of pupils to participate in economic learning, particularly in abstract learning subjects, is relatively small. One of the causes of pupils' low interest in learning is due to the lack of interesting and inappropriate learning media with pupils' needs in learning economics. The purpose of this study is to evaluate how the use of electronic comics affects the interest of Grade XI pupils in learning the topic of wage system material in economics subjects at SMAN 3 Pasuruan. A mixed method approach that combines a quantitative approach with a quasi-experimental model through data collection instruments in the form of surveys, pre-tests, post-tests in control and experimental classes. In addition, this study used a qualitative approach through observation and interview instruments. The results of the research show that electronic comic books can increase students' understanding of and interest in economic subjects, especially on the topic of the wage system material. The effectiveness of electronic comic learning media significantly contributes to the learning of abstract material through appropriate and interesting visualization